Institutional Profile: The ATMP Manufacturing Community (amc). (May 2012) - Foley, Lucy; Callens, Sarah; Osborne, Angela
This article describes the emergence, during 2011, of a community of best practice for the GMP manufacture of cellular therapies in the UK. The community originated in response to the anticipated demand for manufacturing capability as the UK increases its throughput of successful cell therapies. The community will catalyze the development of robust manufacturing processes essential to establishing the cell therapy industry in the UK. The Advanced Therapy Medicinal Product (ATMP) Manufacturing Community (amc) was formed in September 2010 as a community of best practice for cell therapy manufacturing in the UK. During 2011, the amc held three technical meetings, established an online presence via a website, Twitter and LinkedIn and now has 191 members. The amc aims to share nonconfidential information, develop best practice, inform and influence. The amc is also well placed to showcase UK GMP cell therapy manufacturing capability, which is currently well distributed and mostly focused on small-scale manufacture for clinical trials. The amc welcomes and encourages anyone with an interest in cell therapy manufacture to join.